Methodological proposal for an inclusive education: Co-design of a training in digital skills with refugee women - Bueno Doral, Tamara; Francia Ferrero, Rut; García-Castillo, Noelia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Communication technologies and digital literacy can be factors of exclusion among vulnerable groups. Through a practice of social inclusion designed with participatory methodologies, a transdisciplinary team has offered to a group of refugee women in situations of special vulnerability a training program that, aimed at entrepreneurship and job placement, fostered the acquisition of digital skills. In addition, the authors present a service-learning experience with university students that has favored the social inclusion of the refugee women at university and the real training of these formal education students.